Challenges of Women Employees in the Managerial Cadre in Indian IT, Civil and Electronics Industry: An Analysis - Pooja Misra; Kanika Sirohi (Australasian Accounting, Business and Finance Journal, 2019)
India was ranked 120th by World Bank from a list of 131 countries as far as female workforce participation in 2017 is concerned (Venkatesh, 2017). Looking at it from a demographic level, there are only a few states which have a women workforce larger than the men workforce. The low percentage of working women is both a social and economic loss. According to a survey, it was seen that working women form an integral part of the junior management level comprising 16%, while women comprise only 4% each at the middle and senior levels and as far as organizational leadership positions (CEOs) are concerned they represent only 1%. This suggests that that women’s entry is proportionately large but their progression is very slow (Center for Social Research, 2009). Interestingly, there has been little research done in India around the impact of the challenges that women employees in the managerial cadre face which subsequently has a negative influence on their productivity and efficiency. During the course of this research, external factors such as the glass ceiling, discrimination at the work place, unfriendly organizational policies or internal factors like work-life balance, personal capability and perception and family and also societal factors were identified which present a challenge for women employees. The study aims to investigate the impact of these factors on women employees in terms of their efficiency and productivity (Jamali D. , 2006). The research would be conducted for women employees in the managerial cadre in the IT, Civil and Electronics sectors across the country.
Keywords: India; Women employees; glass ceiling; discrimination; unfriendly policies; work-life balance; personal capability and perception; family and societal factors; productivity and efficiency.